The responsibility of electronic cigarette (e-cigarette) business operators who do not include information labels and warnings according to Law Firm Tomi Sihotang & Partners - Purba, Roganda Helena Sanzelina; Simamora, Janpatar (The Future of Education Journal, 2025)
Electronic cigarettes are a development of traditional cigarettes that have switched to electronic form, although their safety is still a question. This research aims to analyze consumer protection for e-cigarettes that do not include information labels and health warnings on their packaging, and to evaluate the regulations governing health information on e-cigarettes in Indonesia. The data in this research was collected through library and field research methods. Literary research was carried out to obtain secondary data by studying various literature and relevant laws and regulations. The research methods used include a normative juridical approach, namely positive legal studies related to existing problems, as well as empirical juridical, which focuses on researching real conditions in society to identify and collect the necessary facts and data. The research results show that sellers who do not include the dangers of cigarettes to the body and e-cigarette liquids. This practice causes losses to consumers and also violates the provisions contained in Law Number 8 of 1999 concerning Consumer Protection and Government Regulation Number 109 of 2012 which regulates the safety of addictive substances in tobacco products.